Law Enforcement Against Organized Illegal Mining in the Jurisdiction of the East Kalimantan Regional Police - Supriyadi, Ahmad; Marwiyah, Siti; Amiq, Bachrul; Prawesthi, Wahyu (Lex Journal : Kajian Hukum dan Keadilan, 2023)
Organized illegal mining constitutes a serious criminal offense that inflicts substantial economic losses upon the state, causes extensive environmental degradation, and undermines the rule of law. This study aims to analyze the effectiveness of law enforcement against organized illegal mining within the jurisdiction of the East Kalimantan Regional Police and to identify strategic measures for its optimization. Employing a normative juridical approach complemented by empirical juridical methods, this research integrates theoretical analysis with field data to examine the dynamics of and obstacles to the law enforcement process. The theoretical framework draws upon Soerjono Soekanto's theory of law enforcement and John Rawls' theory of justice as the primary analytical foundations. The findings reveal that law enforcement efforts continue to confront significant challenges, including weak interagency coordination, limited institutional resources, and the resilience of well-protected organized criminal networks. Furthermore, the vast and geographically challenging terrain of East Kalimantan further compounds the complexity of enforcement operations. This research recommends the adoption of a more integrative law enforcement approach encompassing institutional strengthening, capacity building of law enforcement personnel, and the formulation of regulations more responsive to evolving organized crime patterns. It is anticipated that the findings of this study will serve as a reference for reformulating more effective, equitable, and sustainable criminal law enforcement strategies to address organized illegal mining in Indonesia.